エンダビーランド・リーセルラルセンサン チイキ チガク チョウサタイ ホウコク 1996-97 (JARE-38) - 石塚, 英男; イシズカ, ヒデオ; 三浦, 英樹; ミウラ, ヒデキ; 高田, 将志; タカダ, マサシ; 石川, 正弘; イシカワ, マサヒロ; Zwartz, Daniel Peter; 鈴木, 里子; スズキ, サトコ; 外田, 智千; et al. (1997)
P(論文) 第38次南極地域観測隊(JARE-38)はエンダビーランド・リーセルラルセン山地域で地質および地形の野外調査を1996年12月16日から1997年2月18日までの65日間行った。この野外調査は「東南極のリソスフェアの構造と進化研究計画(SEAL計画)」の初年度の活動である。野外調査は4名の地質班と3名の地形班によって実施された。それぞれの班は地質学あるいは地形学的調査を行い, 約3500kgの学術試料を採取した。本報告では, 計画立案の過程から実施経過までの概要および問題点を主に設営面を中心として詳述し, あわせて野外調査の概要を報告する。 The 38th Japanese Antarctic Research Expedition (JARE-38) performed field work on geology and geomorphology in the Mt. Riiser-Larsen area, Enderby Land, for 65 days from December 16,1996 to February 18,1997. This was a first-year activity of the SEAL (Structure and Evolution of East Antarctic Lithosphere) project. The field work was conducted by two groups, one consisting of four geologists and the other of three geomorphologists. Each group carried out the geological and geomorphological surveys, respectively, and collected scientific samples totaling about 3500kg. This report gives details of the plan and actual logistics, and also summarizes the preliminary results of the field work. departmental bulletin paper